Measurement of thermal conductivity and thermal contact resistance in composite materials for space applications. (4th August 2014) - Marchetti, M.; Testa, P.; Torrisi, F.R.
An apparatus has been designed for measuring thermal conductivity and thermal resistance in vacuum as a function of the applied pressure and of the average temperature at the interface. Results are reported concerning metals such as stainless steel, aluminium and copper, and composite materials such as glass and carbon fibre–epoxy for space applications. The pressure ranged from 0 to 28 × l0 6 Pa and the temperature from 30–90°C. As expected, thermal resistance was seen to decrease with increasing pressure. Resulting uncertainties turn out to be rather high (between 10 and 40%) but still compatible with normal design requirements